2021
DOI: 10.1186/s12909-021-02842-1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching plain language to medical students: improving communication with disadvantaged patients

Abstract: Background Low health literacy underpins health inequality and leads to poor adherence to medical care and higher risk of adverse events and rehospitalization. Communication in plain language, therefore, is an essential skill for health professionals to acquire. Most medical education communication skill programs focus on verbal communication, while written communication training is scarce. ETGAR is a student delivered service for vulnerable patients after hospital discharge in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…First, the proposed curriculum adopted multidimensional indicators, such as conception and evaluation, empathy and acceptance, communication and interaction, as well as medical information and shared decision-making. Other previous studies did not include such comprehensive indicators and most lacked shared decision-making aspects [ 26 29 , 35 , 36 ]. Second, we applied various student-centric teaching methods and created interesting materials for innovative teaching, including inquiry-based learning, observational learning, group discussion, game-based learning, and role-play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the proposed curriculum adopted multidimensional indicators, such as conception and evaluation, empathy and acceptance, communication and interaction, as well as medical information and shared decision-making. Other previous studies did not include such comprehensive indicators and most lacked shared decision-making aspects [ 26 29 , 35 , 36 ]. Second, we applied various student-centric teaching methods and created interesting materials for innovative teaching, including inquiry-based learning, observational learning, group discussion, game-based learning, and role-play.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a comparative group was noted in previous intervention studies, which revealed insufficient evidence to support the effectiveness of the training curriculum. In the recent years, some research on training in health literacy focused on medical students and revealed a positive effect, but lacked comprehensive intervention approaches or evaluation methods [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of this bypass to overcome the disconnect between the hospital and community was implemented in the ETGAR program (36) aimed at reducing recurrent admissions following discharge from hospital. ETGAR, also developed by the medical school, uses medical students to visit patients and provide guidance following discharge (36). As demonstrated by ETGAR, there is a need for improved coordination and collaboration between hospital and community.…”
Section: Discussionmentioning
confidence: 99%
“…The responsibility for patients' and carers' education needs to be shared with other HCPs beyond the hospital and home healthcare setting. Crucial written information should be provided in plain language [21,26,27], easily irrespective of the literacy level and should be standardized among hospital, primary care and homecare understandable teams. This shared responsibility and reinforcement of education at distinct moments has potential to improve patients' acceptance of the HRT and long-term adherence [28].…”
Section: Discussionmentioning
confidence: 99%